Hypolipidemia associated with inactivation of TM6SF2 is due to decreased VLDL-lipids secretion. (14th October 2021) - Luo, F; Smagris, E; Fletcher, J A; Cohen, J C; Hobbs, H H
Abstract: Background: A missense variant in Transmembrane 6 Superfamily Member 2 [TM6SF2 (E167K)] is associated with reduced plasma lipid levels and protection from coronary atherosclerosis. The substitution of lysine for glutamate at residue 167 is associated with a marked decrease in TM6SF2 protein expression, consistent with a loss-of-function mutation. However the biological role of TM6SF2 is not known, and the mechanism(s) responsible for the hypolipidemia associated with mutation gene has not been fully defined. To elucidate the pathological mechanism for the hypolipidemia associated with TM6SF2 deficiency, we inactivated Tm6sf2 in mice and rats. Methods: Tm6sf2−/− mice were generated as described previously. Two lines of Tm6sf2−/− rats with different frameshift mutations in exon 1 were generated using CRISPR/Cas9 technology. Primary hepatocytes were isolated from WT and Tm6sf2−/− mice for microscopy. Rats were fasted 16 or 4 hours and tissues were collected on ice for cell fractionation, and in liquid nitrogen for biochemical analyses. Frozen samples were stored at −80°C for subsequent analyses. Result: In both mice and rats, inactivation of Tm6sf2 recapitulated the phenotype of humans with the E167K substitution: steatosis, reduced plasma lipid levels, and transaminitis. The phenotype was readily apparent in animals fed chow diets. Both species had reduced secretion of VLDL-TG, as determined by TRITON WR1399 injection, with no decrease in secretion of ApoB. Experiments in isolated perfused livers from WT and Tm6sf2−/− mice confirmed that the decreased TG secretion observed in intact animals reflected reduced TG secretion from the liver. Lipidomic analysis of the liver perfusates by by LC-MS indicated that secretion of cholesteryl esters, and phospholipids was also decreased in the KO animals. Taken together, these findings are consistent with a role for TM6SF2 in lipidation of ApoB-containing lipoproteins. To further elucidate the function of TM6SF2, we used fluorescence microscopy and cell fractionation to determine the subcellular localization of the protein. Microscopic analysis showed that TM6SF2 co-localized with ER and Golgi markers, but cell fractionation studies indicated that the protein is located primarily in the smooth ER. The ratio of TG to ApoB was lower in Golgi fractions from TM6sf2−/− rats than in corresponding fractions from WT animals. Conclusions: Since the sequela of TM6SF2 inactivation are already apparent in the Golgi, we speculate that TM6SF2 promotes lipidation of VLDL in a pre-Golgi compartment. We are currently performing additional studies to further define the specific mechanism whereby TM6SF2 promotes lipidation of ApoB-containing lipoproteins. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): National Institutes of Health